Railways & Music - Winterson, Julia (University of Huddersfield Press, 2022)
When the Stockton & Darlington Railway opened in 1825, it was the first steam-powered railway to carry passengers. Since then there has been no shortage of music connected with trains and railways: orchestral pieces and popular songs describing railway journeys; those that celebrate the opening of a new line; worksongs and blues describing the hardship of building the railroads, even the first use of sampled music used railway sounds as its source. The railway has inspired countless pieces of music from the pastoral serenity of the Flanders and Swann song 'Slow train' to the shrieking horror of holocaust trains in Steve Reich's Different Trains. This is the first book to give a comprehensive coverage of music connected with the railways. In the nineteenth century, thousands of miles of railway lines transformed time, space and distance. Across Europe composers celebrated with music such as waltzes and polkas, cantatas, piano pieces and saucy music hall songs. Moving into the twentieth century, iconic twentieth-century works, such as Britten's Night Mail and Honegger's Pacific 231, captured the sounds of locomotives. Railways and trains are so deeply ingrained in the popular imagination that they feature in hundreds, possibly thousands, of popular songs. In North America, early railroad songs told of hoboes, heroes, villains, and train wrecks and the sounds of the railroad were heard in boogie-woogie, blues, gospel, jazz, and rock music. In total, this book describes over 50 pieces of classical music and covers more than 250 popular songs.